2008
DOI: 10.1242/dev.015149
|View full text |Cite
|
Sign up to set email alerts
|

The mutationROR2W749X, linked to human BDB, is a recessive mutation in the mouse, causing brachydactyly, mediating patterning of joints and modeling recessive Robinow syndrome

Abstract: Mutations in ROR2 result in a spectrum of genetic disorders in humans that are classified, depending on the nature of the mutation and the clinical phenotype, as either autosomal dominant brachydactyly type B (BDB, MIM 113000) or recessive Robinow syndrome (RRS, MIM 268310). In an attempt to model BDB in mice, the mutation W749X was engineered into the mouse Ror2 gene. In contrast to the human situation, mice heterozygous for Ror2 W749FLAG are normal and do not develop brachydactyly, whereas homozygous mice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 44 publications
3
35
0
1
Order By: Relevance
“…premature regression of the AER was observed in Ror2 W749X/W749X or Ihh E95K/E95K mice (6,9). At E14.5, the remaining distal cartilage is undergoing the program for tip formation in Ror2 W749X/W749X mice, at the appropriate time as in WT mice, concordant with a reactivation of Ihh expression.…”
Section: Discussionmentioning
confidence: 89%
“…premature regression of the AER was observed in Ror2 W749X/W749X or Ihh E95K/E95K mice (6,9). At E14.5, the remaining distal cartilage is undergoing the program for tip formation in Ror2 W749X/W749X mice, at the appropriate time as in WT mice, concordant with a reactivation of Ihh expression.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, there are, to our knowledge, no reports of recessive Robinow syndrome male patients having reproduced (reviewed in Patton and Afzal [73]). Importantly, knockin mice harboring a ROR2 W749X mutation have been shown to model adult recessive Robinow syndrome, and adult male mice display reduced fertility [77]. Adult testes from ROR2 W749X homozygous males were smaller than those of wild-type, a phenotype caused by focal degeneration of seminiferous tubules with reduced number of spermatogonia and lack of spermatocytes [77].…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype, presence of a terminal phalanx but absence of more proximal structures is seen in human brachydactylies type A1, A2 and in some cases of BDB1. However, analyses of mouse models for BDA1 and BDB1 (Raz et al, 2008;Gao et al, 2009) have found no indication of AER/Fgf involvement in the pathogenesis of these syndromes. It thus appeared likely that another mechanism must be involved in the elongation of the digits, namely by driving chondrogenesis in a distally orientated manner.…”
Section: Elongation Of the Initial Condensation By Distally Directed mentioning
confidence: 99%
“…Witte et al (2010b) analyzed mouse mutants harboring a targeted insertion of a human mutation in the endogenous Ror2 locus (Ror2 p.W749X), causing severe BDB1 phenotypes. Homozygous Ror W749X/W749X mice lack the medial phalanges, this phenotype has previously been considered to be a defect in the formation of the last interphalangeal joint (Raz et al, 2008). Witte et al (2010b) showed that preceding the failure of joint formation, elongation of the phalangeal condensation was severely impaired.…”
Section: Segmentation Of the Digitsmentioning
confidence: 99%